THE INGREDIENTS OF PIONEERING PERFORMANCE AND THEIR REFLECTION IN ENHANCING DIGITAL MANAGEMENT/ KIRKUK CEMENT COMPANY A MODEL - Mohammed Hussein Gharbi (Scholar Express Journals, 2024)
The present research aims to identify business performance trends as long-term creative trends, integrated into work, objective vision and rational analysis, and integral to perception, in an attempt to influence organizational activities and build positive behaviors for improve digital management in business organizations. Therefore, they are more creative and capable of overcoming risks and solving problems. problems and be more capable of undertaking competitive adventures
Keywords: Entrepreneurial performance; digital management